SEJARAH ADMINISTRASI DAN KEAGAMAAN DESA BOHABAK KABUPATEN BOLAANG MONGONDOW UTARA - Babay, Suprianto (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2022)
This article reviews the early history of Bohabak village in East Bolaang mongondow, and examines the socio-religious history of the Bohabak community with historical evidence such as mosques and churches. The purpose of this research is to reveal the history of Bohabak village and its socio-religious aspects which have not been implemented so far. The method used by the author is the historical method which consists of four stages: the first is heuristic or data collection, the second is source criticism to objectively filter historical data, the third is interpreting data, and the last is historiography or historical writing. The results of this study describe that Bohabak Village is one of the villages in North Bolaang Monggondow Regency which existed around 1600 AD. At that time this area was not known or not known as Bohabak village, because at that time it was still known as the Makopag kingdom, called the makopag kingdom because at that time there was a group of primitive humans. In terms of religious life, the people of Bohabak Village know that religious tolerance is so strong, this is evidenced by the creation of mutual cooperation among religious adherents, mutual respect when adherents of other religions carry out worship activities and even maintain their security